Women's writing in exile - Davidson, E (2010)
﻿ Despite the recent increase in scholarship on the subject of the female experience in exile, there is still much to be done. Exile scholars now have at their disposal an abundance of broad, general overviews of the circumstances and fates of displaced women writers, but a dearth of scholarship that considers specific literary works in an individualised fashion still exists. This is especially true of those female writers who have only recently been 'rediscovered', such as the three under discussion in this thesis. This thesis explores in detail the exile writings of Veza Canetti, Anna Gmeyner, and Lili Korber, about which little scholarship exists, and uses them as case studies to illuminate the situation of exiled women writers in general The exile works of these three authors repay study both for their own literary merits and for what they can tell us about the individual experience of exile. In their broad similarities, these writers also provide us with case studies of the larger experience of authorial exile - particularly, but by no means exclusively, the gendered experience - that allow us to derive more general lessons about the influence of forced flight on literary art. By giving due consideration to work produced in exile, this thesis calls into question some of the generalisations commonly found in recent scholarship and demonstrates that, despite hardsrnps and setbacks and contrary to common scholarly contention, all three women continued to write well into their exile years and that in those years they took their writing in new, skilful, and creative directions.